Carbapenem resistance in Enterobacterales bloodstream infections among children with cancer or post-haematopoietic stem cell transplant: a retrospective cohort study (2023)
Background Risk factors for carbapenem resistance in Enterobacterales bloodstream infections among children with cancer or post-HSCT have not been thoroughly explored. Methods All children with cancer or post-HSCT who developed Enterobacterales bloodstream infections in two cancer referral centres in major Colombian cities between 2012 and 2021 were retrospectively examined. When the infection episode occurred, carbapenem resistance mechanisms were evaluated according to the available methods. Data were divided in a training set (80%) and a test set (20%). Three internally validated carbapenem-resistant Enterobacterales (CRE) prediction models were created: a multivariate logistic regression model, and two data mining techniques. Model performances were evaluated by calculating the average of the AUC, sensitivity, specificity and predictive values. Results A total of 285 Enterobacterales bloodstream infection episodes (229 carbapenem susceptible and 56 carbapenem resistant) occurred [median (IQR) age, 9 (3.5–14) years; 57% male]. The risk of CRE was 2.1 times higher when the infection was caused by Klebsiella spp. and 5.8 times higher when a carbapenem had been used for ≥3 days in the previous month. A model including these two predictive variables had a discriminatory performance of 77% in predicting carbapenem resistance. The model had a specificity of 97% and a negative predictive value of 81%, with low sensitivity and positive predictive value. Conclusions Even in settings with high CRE prevalence, these two variables can help early identification of patients in whom CRE-active agents are unnecessary and highlight the importance of strengthening antibiotic stewardship strategies directed at preventing carbapenem overuse.